PERHITUNGAN OIL LOSSES PADA SPENT BLEACHING EARTH UNIT FILTRATION SECTION ALAT NIAGARA FILTER PADA REFINERY PLANT DI SUMATERA BARAT - Fikri, Muhammad; Desniorita, Desniorita (Politeknik ATI Padang, 2021)
CPO is a crude oil obtained by extracting the palm fruit’s skin. CPO still contains both soluble and insoluble impurities in the oil. The purpose of palm oil purification is to efficiently convert crude palm oil into high-quality edible oil by removing undesirable impurities to an acceptable level. This also means that the loss of desirable components should be minimized. The refining process, which transforms crude palm oil (CPO) into edible oil, includes degumming, bleaching, and filtering to remove gum and unwanted components. In the Niagara filter, oil losses often occur, where the lost oil is usually discarded with SBE (Spent Bleaching earth). The extent of oil losses also affects the yield of RBDPO. Therefore, it is necessary to analyze total oil losses in the Niagara Filter process and identify the factors influencing these losses. The analysis results show that oil losses in SBE are directly proportional to the dosing of BE (Bleaching earth) in the bleaching process. The highest oil loss value in the Niagara Filter was 0.180%, while the lowest was 0.129% (company standard <0.14%). High oil losses can negatively impact the yield of the produced oil.